PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI (Glycine max L.) YANG DIBERI PUPUK GUANO DAN MULSA ALANG-ALANG - Sarawa, Sarawa; Nurmas, Andi; Dasril, Muh AJ (Jurnal Agroteknos, 2012)
The objective of this study was to study the growth and yield of Soybean (Glicine max L. Mer) treated by guano fertilizer and tall grass mulch, conducted from July to September 211 in Experimental Garden of Agriculture, Univesity of Haluoleo, Kendari. The study wass arrange on Randomized Completely Block Design in factorial pattern, consisting of two factors. The first factor was guano fertilizer (G), consisting of four level i.e. without guano fertilizer (G0), 4 t ha-1of guano fertilizer (G1), 8 t ha-1of guano fertilizer(G2), and 12 t ha-1guano fertilizer (G3). Second factor is was tall grass mulch(M) consisting of four level i.e. without mulch(M0), 5 t ha-1,(M1), 10 t ha-1,(M2), and 15 tha-1. (M3). Eachcombination was repeated tree times as block so there were 48 experimental units. Variabel observed were plant height, number of pods formed, number of seed planting, dry weight of 100 seed and yield in t ha-1. The results of the research indicate that the effects of interaction between guano ferlizer and tall grass mulch were significantly difference on plant height, number of pods formed, number of seed planting, dry weight of 100 seed adn yield in t ha-1. Keywords : soybeans, guano fertilizer, mulch